Digital Transformation in Civil Servant Competency Development at BPSDMD Banten Province - Budi Sihabudin; Fatulloh Fatulloh; Aisyah Mauliddina (HK-Publishing, 2024)
Abstract Digital transformation within the bureaucracy has become an urgent necessity for achieving excellent Electronic-Based Government Systems (SPBE). This study aims to analyze the implementation, obstacles, and impact of digital transformation on the competency development of State Civil Apparatus (ASN) at the Regional Human Resources Development Agency (BPSDMD) of Banten Province. A descriptive qualitative method was employed, utilizing data collection techniques such as in-depth interviews, observation of e-learning platforms, and document analysis. The results indicate that the digitalization of training systems—specifically through the